2021
DOI: 10.1016/j.jenvp.2021.101623
|View full text |Cite
|
Sign up to set email alerts
|

Influencing climate change attitudes in the United States: A systematic review and meta-analysis

Abstract: We thank Paul Piff, Joanne Zinger, and Steven Davis for their insightful feedback at various stages of this project. We also thank the primary study authors who were willing to share their data with us. We thank anonymous reviewers for their help with the manuscript, particularly with contextualizing the size of the summary effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 169 publications
6
42
0
1
Order By: Relevance
“…Our data offer only indirect evidence for this complacency model, as we did not measure perceived risk or distress subsequent to our efficacy message. In passing, we note that this account may also explain a striking finding from the metaanalysis by Rode et al (2021) cited above, which is that negative interventions-those that seek to reduce belief in climate change-are associated with much larger effect sizes than positive interventions. People may be attracted to information that makes climate change seem less of an urgent problem, whether that information entails reassurance that the problem can be tackled or a downplaying of the problem itself.…”
Section: Direct and Indirect Effects Of Climate Communication Messagesmentioning
confidence: 67%
See 2 more Smart Citations
“…Our data offer only indirect evidence for this complacency model, as we did not measure perceived risk or distress subsequent to our efficacy message. In passing, we note that this account may also explain a striking finding from the metaanalysis by Rode et al (2021) cited above, which is that negative interventions-those that seek to reduce belief in climate change-are associated with much larger effect sizes than positive interventions. People may be attracted to information that makes climate change seem less of an urgent problem, whether that information entails reassurance that the problem can be tackled or a downplaying of the problem itself.…”
Section: Direct and Indirect Effects Of Climate Communication Messagesmentioning
confidence: 67%
“…Behaviour is hard to change, and climate behaviour is no exception. A recent meta-analysis of climate change attitude interventions has confirmed that these interventions are less effective at influencing policy attitudes than beliefs (Rode et al, 2021).…”
Section: Direct and Indirect Effects Of Climate Communication Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, van der Linden et al (2019) report a d = 0.09 main effect of the consensus message on policy support. More broadly, a meta-analysis of climate messaging effects conducted byRode et al (2021) reports that policy attitudes are more difficult to experimentally shift than other climate-related attitudes. The pooled effect of expert consensus studies on climate attitudes (g = 0.09) was robust though relatively small, but in line with the meta-analytic effect size for all climate messaging interventions examined in the analysis (g = 0.08), from moral frames to psychological distance manipulations.…”
mentioning
confidence: 99%
“…The effects reported in the current study also result from just a single exposure. Implemented at scale small messaging effects can have a discernible impact on public opinion (see discussion in:Landrum & Slater, 2020;Rode et al, 2021;van der Linden et al, 2019). More engaging and repeated consensus messaging campaigns incorporating visual elements or humor may prove more…”
mentioning
confidence: 99%